Coordination Polymers with Intriguing Photoluminescence Behavior: The Promising Avenue for Greatest Long‐Lasting Phosphors. Issue 20 (22nd May 2018) - San Sebastian, Eider; Rodríguez‐Diéguez, Antonio; Seco, Jose M.; Cepeda, Javier
Abstract : Luminescent coordination polymers (CPs) are known for their unique abilities to provide tunable emission processes originated at the interplay between their infinite inorganic and organic constituents combined in endless ways, thus yielding smart molecule‐scaled materials to be processed as photodevices, sensors, optical storage systems or even logic gates. Nonetheless, most of these applications demand the occurrence of persistent luminescence to prevent background interference with the fluorescence signal. This is the reason why attention has been recently shifted to CPs exhibiting long‐lasting phosphorescence (CP‐LLPs), which imbues these crystalline solids with a long‐lived emission that is traceable by the human eye. The large interest awakened by these materials opposes with their difficulty to being achieved compared to dominant fluorescent CPs, probably derived from their challenging design. In this microreview we give an overview of the CP‐LLPs reported so far with the aim of deciphering some hints that enable this behavior while their potential applications are also discussed. Abstract : CP‐LLPs are luminescent materials exhibiting persistent emissions that last for several seconds. Accompanied by a brief description of reported CP‐LLPs, this review provides some hints towards their rational design and discusses their potential applications.